1972
DOI: 10.1071/ar9721093
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde as a silage additive. I. The chemical composition and nutritive value of frozen lucerne, lucerne silage, and formaldehyde-treated lucerne silage

Abstract: Formaldehyde-treated silages, frozen lucerne, and untreated silage were prepared from a lucerne stand and offered to Merino wethers. Formalin was applied at rates of 16.6, 24.9, and 33.1 g formaldehyde per 100 g crude protein. Formaldehyde-treated silages had significantly lower concentrations of ammonia nitrogen and total and individual organic acids than did untreated silage, and hence the ensiling fermentation was inhibited by formaldehyde. Formaldehyde treatment of lucerne partly protected plant proteins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
3

Year Published

1975
1975
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 7 publications
4
12
0
3
Order By: Relevance
“…These effects of formic acid and the mixture of formic acid and formaldehyde on silage fermentation were similar to those reported by others. 4,5,11,12 Generally, when control silages are well preserved, formic acid and formaldehyde have the effect of restricting the formation of lactic and acetic acids and conserving the soluble carbohydrate component. 13 In the present experiment the concentrations applied to the herbage of formic acid, when applied alone, or of formaldehyde (81 g kg À1 herbage crude protein) were higher than normally used in commercial practice and therefore the restriction of fermentation encountered would rarely be seen in practice.…”
Section: Results and Discussion Herbage And Fermentation Characteristicsmentioning
confidence: 99%
“…These effects of formic acid and the mixture of formic acid and formaldehyde on silage fermentation were similar to those reported by others. 4,5,11,12 Generally, when control silages are well preserved, formic acid and formaldehyde have the effect of restricting the formation of lactic and acetic acids and conserving the soluble carbohydrate component. 13 In the present experiment the concentrations applied to the herbage of formic acid, when applied alone, or of formaldehyde (81 g kg À1 herbage crude protein) were higher than normally used in commercial practice and therefore the restriction of fermentation encountered would rarely be seen in practice.…”
Section: Results and Discussion Herbage And Fermentation Characteristicsmentioning
confidence: 99%
“…On its own, formaldehyde has not always prevented clostridial fermentation (Wilkins, 1978) and to overcome this, formic acid is added to the formaldehyde (Wilson and Wilkins, 1977). Dry matter intake of lucerne silage has been increased by formaldehyde treatment (Valentine and Brown, 1973;Wilkins et ai, 1974;Barry et ai, 1978a) but unlike formic acid it has been found that high rates depress intake (Brown and Valentine, 1972;Demarquilly et ai, 1977).…”
Section: Lucerne Silagementioning
confidence: 99%
“…There is ample evidence that the voluntary intake of silage by ruminants is limited by the products of fermentation (Wiikins et al 1971;Brown and RadcIifiFe, 1972). The treatment of herbage with additives containing formaldehyde has produced silages containing low levels of both fermentation acids and the products of protein degradation (Brown and Valentine, 1972;Wiikins et al, 1974b). Further, the addition of formaldehyde to ensiled and dried grass has been shown to reduce dietary protein breakdown in the rumen and to lead to increased total flow of amino nitrogen to the small intestine (Beever et al, 1976).…”
Section: Introductionmentioning
confidence: 99%